Preparation of microspheres with sustained ketoprofen release by electrospray for the treatment of aseptic inflammation - Dai, Xinyi; Nie, Wei; Duan, Chuanyou; Shen, Yi (Frontiers in Bioengineering and Biotechnology, 2024)
The treatment of aseptic inflammation has always been a clinical challenge. At present, non-steroidal drug-loaded microspheres have been widely used in the treatment of aseptic inflammation due to their excellent injectable and sustained release capabilities. In this study, ketoprofen-loaded shellac microspheres (Keto-SLAC) were prepared by electrospray. Alterations of Keto-SLAC morphology was observed in response to changed shellac concentration in ethanol solution through electrospray. Further examination revealed that ketoprofen presented as amorphous solid dispersion in the shellac microspheres. Most importantly, it was also shown that ketoprofen can be slowly released from the shellac matrix for up to 3 weeks. In vitro cell experiments verified that the microspheres had favorable cell compatibility. We therefore proposed that the prepared microspheres, being readily available in use in a variety of clinical settings through topical application, have promising therapeutic potential for the treatment of aseptic inflammation.